Mathematics Education Resources on the Internet - Mary DeCarlo (Issues in Science and Technology Librarianship)
This guide is designed primarily for the mathematics educator, whether in the role of teacher or as the student in a college education program. The majority of resources included here focus on primary and secondary education, but many may easily apply to college level. Sections in this guide describe the principal Internet sites in each category that provide high quality information. These resources have been chosen based on currency and depth and breadth of coverage. All selected sites provide their resources freely and, with only two exceptions, are hosted by educational institutions, government offices, or non-profit organizations. This guide updates and expands on previous math education bibliographies and focuses on the educator as researcher, as well as instructor. Resources were selected to facilitate the research of the educator and librarian.